Digital Twins and Urban SDGs Simulating Smart Cities for Sustainable Development (International Journal of Environmental Sciences, 2025)
Digital Twins has transformed the way an urban environment can be managed and operated by developing digital twins of physical systems through real-time emulation. With the urbanization phenomenon occurring around cities, which is accompanied by population growth, climate changes, and other resource limitations, including Digital Twins in the process of urban planning has become one of the most important facilitators of reaching the United Nations Sustainable Development Goals (SDGs). This paper addresses the possibility to use Digital Twin technologies in order to simulate, monitor, and optimise a range of elements of smart cities, including infrastructure, energy systems, mobility, and environmental health to be in the harmony with the urban SDG goals. Using an extensive analysis of existing implementations, simulation frameworks, and impact analysis frameworks, the paper offers a design methodology of SDG-driven Digital Twins of cities. The outcomes show how these systems have the potential to enhance policy-making, active citizens involvement, and proper utilization of resources. The discussion provides the barriers and perspectives to global urban sustainability that needs to be done to scale such technologies.